Refitting an X-ray diffraction system for combined GIXRF and XRR measurements. (December 2020) - Ingerle, Dieter; Artner, Werner; Hradil, Klaudia; Streli, Christina
Abstract : A commercial Empyrean X-ray diffractometer was adapted for combined grazing incidence X-ray fluorescence analysis (GIXRF) measurements with X-ray reflectivity (XRR) measurements. An energy-dispersive silicon drift detector was mounted and integrated in the angle-dependent data acquisition of the Empyrean. Different monochromator/X-ray optics units have been compared with the values obtained by the Atominstitut GIXRF + XRR spectrometer. Data evaluation was performed by JGIXA, a special software for combined GIXRF + XRR data fitting, developed at Atominstitut. A sample consisting of a 50 nm nickel layer on a silicon substrate was used to compare the performance criteria (i.e. divergence and intensity) of the incident beam optics. An Empyrean X-ray diffractometer was successfully refitted to measure both GIXRF and XRR data.